The Construction of Educational Interaction Models in Pesantren and Its Relevance to Contemporary Islamic Education - Ahmad Mahfudzi Mafrudlo; Zuhratul Aini Mansur; Ghilmanul Wasath; Muhammad Ersyad Muttaqien (Universitas Muhammadiyah Malang, 2023)
This paper aims to elaborate on the significance of educational interaction in Islamic Education institutions known as Pesantren. As in the Islamic Education in Indonesia that applied integration between technological developments, educational interaction, and educational transformation. It's just that the values of the implementation process of this integration cause discontinuity between interaction and transformation of knowledge. The essence of the significance of the Islamic Education model in the Pesantren needs to be revitalized, it is very relevant to how the process and dynamics of Islamic Education in the modern era. The educational interaction model applied in Pesantren is a reference and guideline for all parties and educational institutions and is important to be constructed in order to obtain proportional and comprehensive Islamic Education. This research was initiated for contributive things and is a type of library research. The Study employed a qualitative study design to capture a real-life context of the Islamic education of Pesantren in playing its role. Finally, it will find various opinions and perspectives from authors who explain and review the existence of Islamic Education institutions that have implemented educational interactions. The finding revealed that the pattern of educational interaction carried out in pesantren focuses on two things: educational interaction in daily activities and educational interaction in the system. The model of implementing educational interaction is comprehensively understood by all parties in the pesantren so that the reality of Islamic education is formed for the shake of the sustainability of the education process.